Epigenetic Treatment of Myelodysplastic Syndromes and Acute Myeloid Leukemias - Leone, Giuseppe (Bentham Science Publishers Ltd., 2008)
Epigenetic mechanisms affecting chromatin structure contribute to regulate gene expression and assure the inheritance of information, which are essential for the proper expression of key regulatory genes in healthy cells, tissues and organs. In the medical field, an increasing body of evidence indicates that altered gene expression or de-regulated gene function lead to disease. Cancer cells also suffer a profound change in the genomic methylation patterns and chromatin status. Aberrant DNA methylation patterns, changes in chromatin structure and in gene expression are common in all kind of tumor types. However, studies on leukemias have provided paradigmatic examples for the functional implications of the epigenetic alterations in cancer development and progression as well as their relevance for therapeutical targeting.